Global, regional, and national burden of gallbladder and biliary tract cancer among adults aged 55 years and older, 2010–2021 - Li, Mingjuan; Li, Jiaguang; Li, Shuangjiang; Zhang, Minmin; Li, Shuang; Zhao, Jiahui; Gan, Tao; Wu, Min; Luo, Shunwen; Liang, Yunying; Li, Qiuyun; Pan, Guangdong; et al. (Frontiers in Nutrition, 2025)
IntroductionGallbladder and Biliary Tract Cancer (GBTC) accounts for a notable proportion of cancer cases worldwide. This study aims to assess the burden of GBTC among aged 55 years and older, enhancing our understanding of its trends and their relationship with Socio-Demographic Index (SDI) across regions and countries.MethodsWe used the data from the Global Burden of Disease study from 2010 to 2021 to analyze GBTC incidence, death numbers, disability-adjusted life years (DALYs) and their respective rates for individuals aged 55 years and older. We also reported the GBTC percentage trend during this period.ResultsThe global incidence and death cases of GBTC changed significantly between 2010 and 2021. Compared to 2010, GBTC incidence and deaths increased by 35.9% and 29.7% individually in 2021. High-income Asia Pacific was the region with the highest age-standardized incidence, deaths, and DALYs in 2021, and China was the country with the largest number of incidence cases, deaths, and DALYs in 2021. Furthermore, the highest age-standardized incidence rate and age-standardized death rate occurred in Japan. Among individuals aged 55 years and older, the highest incident and death cases were observed in 70–74 age group, and females were more suffered from GBTC than males between 2010 and 2021.ConclusionGBTC remains a substantial and growing global health burden, particularly among females and the aged from 2010 to 2021. The absolute number of GBTC cases continued to rise over the past decade in aged 55 years and older.